Nilai-Nilai Pendidikan Islam Dalam Tradisi Batunggu Kubur Di Desa Lok Baintan Kecamatan Sungai Tabuk - Muhamad Ishaac; Laili Mukarram, Muhammad (Tamadduna: Jurnal Peradaban, 2024)
The tradition of batunggu kubur is a cultural practice spread across various regions, showing a diversity of meanings and deeper purposes for the surrounding community. One is in the South Kalimantan Province, especially in Lok Baintan Village, Sungai Tabuk District, Banjar Regency. This article was created to explore them in the tradition of batunggu kubur in the village. The research method used is qualitative field research with a descriptive approach. The data sources in this study are primary data from residents and community leaders of Lok Baintan Village and secondary data from literacy sources. The data collection techniques used are interviews and documentation. This article reviews the origins and development of the tradition of batunggu kubur. It also highlights the role of today's society in carrying out this tradition, and how this practice can influence and reflect social dynamics, moral values, ethics, and culture that include Islamic education it, including several series of Islamic teaching activities for people who have just died.